Outsourcing services in the healthcare sector: balancing risks and benefits - ÇELİK, YUSUF (My University, 2022)
The outsourcing of services in the healthcare sector needs to be thoroughly investigated and comprehensively reviewed to determine the advantages, disadvantages and challenges for healthcare providers. This review explores outsourcing in the context of healthcare services, with the aim of helping managers to understand and facilitate service outsourcing effectively within their healthcare organisations by maintaining the balance between maximising benefits and minimising risks.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)